Multiple brown tumors in primary hyperparathyroidism - Chirihan Ayadi, MD; Safae Lanjery, MD; Hajar Andour, MD; Farah Kamel, MD; Hamza El Qandili, MD; Mendes Papys, MD; Laila Jroundi, MD; Fatima Zahra Laamrani, MD (Radiology Case Reports, 2022)
Brown tumors are benign bone tumors that rarely complicate hyperparathyroidism, manifesting as fibrous and erosive lesions secondary to rapid and localized osteoclast turnover. These lesions are typical of primary hyperparathyroidism, but they are not often observed. We present the case of a 72-year-old woman presenting with asthenia, bone pain, and hemiplegia. Biological analysis showed primary hyperparathyroidism, cervical ultrasound a right parathyroid adenoma that fixed on scintigraphy. When cross-sectional imaging was performed, it revealed multiple bone tumors of the axial and peripheral trunk with spinal cord compression which were diagnosed as brown tumors related to parathyroid adenoma. We illustrate through this case the importance of multidisciplinary imaging techniques before raising the diagnosis, especially in unusual pathologies such as brown tumors.